URBAN DEVELOPMENT AND ITS IMPACT TO AGRICULTURAL SECTOR IN SLEMAN REGENCY, D.I. YOGYAKARTA PROVINCE, INDONESIA - , YOAN ADI WIBOWO SUTOMO; , Giuliano Mingardo, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Extensive urban sprawl process is very common in developing country, including Indonesia. Yogyakarta Municipality as one of the developing city in Indonesia also experienced urban sprawl process that mainly going to the north side where Sleman Regency lies. Sleman Regency is very attractive for urban development because it passed by national road which is economic route that connect main port cities, many famous universities, and many tourism places. On the other hand, Sleman Regency that located in the upper slope of Merapi Volcano also has another function as the water catchment area, conservation area, and agriculture area. That is why the development process in Sleman Regency needs to be controlled and managed to prevent it from harming the environment and agricultural sector. The objective of this research is to identify the urban sprawl pattern and trend then analyze the impact to agricultural sector in Sleman Regency. Agricultural sector can have a direct impact to food security and people normally just analyze it based on statistical data. This research try to combine the statistical data and spatial data to analyze the impact of urban sprawl to agricultural sector based on the pattern and trend of the urban sprawl in Sleman Regency within 15 years period from 1991-2006. This research also try to analyze the local government anticipation to the land conversion that caused by urban sprawl and its impact to agricultural sector with focus on land use planning, land use management, land use monitoring, irrigation system management, and agriculture management. The analysis focuses on the policies, implementation, supporting factors and obstacles and conducted by in depth interview to key persons and document analysis. The research found that there are three patterns of urban sprawl that occur in Sleman Regency in the period 1991-2006, there are concentric pattern in the urban area that directly adjacent with Yogyakarta Municipality, leap frog pattern in the sub urban area around the urban area, especially in the northern part, and linear pattern in the western part of Sleman Regency that mainly caused by the new bridge construction that connects Sleman Regency with Kulon Progo Regency of D.I. Province. The impact of those three urban sprawl patterns to agricultural sector in Sleman Regency is different. Concentric pattern in the urban area change the wet land area that less productive so only productive agriculture land in urban area that survive from land conversion. This condition is suitable with the government plan by developing urban function in this area while still protecting productive agricultural land that supported by technical irrigation system. The linear pattern in the western part of Sleman Regency is not disturbing the irrigation system but the land conversion still give impact to the rice production in this area, especially because this area is the agricultural concentration area. The leap frog pattern that occurs in sub urban area is the urban sprawl pattern that gives many impacts to agricultural sector. This pattern not only cause land conversion but also can disturb the irrigation system network, decrease the productivity of the agricultural land in that area, and lead to more massive land conversion. The local government of Sleman Regency already gives attention to this problem by improving the land management process but still have limitation, especially in database and law enforcement. These two things is the most crucial things to develop in the future to maintain the agricultural and conservation function in Sleman Regency while the urban function can still develop.